Cannabidiol in the Treatment of Epilepsy: A Focused Review of Evidence and Gaps - Silva, Guilherme Diogo; Del Guerra, Felipe Borelli; de Oliveira Lelis, Maira; Pinto, Lécio Figueira (Frontiers in Neurology, 2020)
Approximately one-third of epilepsy patients do not become seizure free with antiseizure medications (ASMs). This treatment gap motivates research for new therapeutic options such as cannabidiol (CBD). CBD differs from other cannabis derivatives because of its consistent efficacy and lack of a psychoactive effect. CBD can be recommended as adjunctive therapy in patients with Dravet and Lennox-Gastaut syndromes. The most common adverse effects (AEs) are drowsiness, reduced appetite, diarrhea and vomiting. Transaminase elevation is the most common AE that leads to CBD discontinuation. Coadministration with valproate may increase the risk of hepatotoxicity. The combination of CBD and clobazam may increase both the effectiveness and the risk of AEs associated with these drugs. The most striking gaps in knowledge are the efficacy and optimal dose of cannabidiol for adults with focal epilepsies, thelong-term safety of CBD use and strategies to improve access to CBD for people living with epilepsy.